Análisis de las mudas en los procesos productivos de la empresa “Caral Ingeniería Mecánica” para el mejoramiento de la eficiencia productiva. En la ciudad de Quito. - Aroca Anchapaxi, Jefferson Stalin (2022)
The actual research was affected in the "Caral Ingeniería Mecánica" enterprise, located Quito city north, specifically, into production area, which are designed and manufactured all kinds machining, into materials, such as nylon, duralon, tempered steel, stainless steel, etc. It was made the proposal of reducing the found seedlings in the entity's production process, through the production tools and lean manufacturing techniques use for improving its productive efficiency. The applied methodology into present work is the inductive method, since it is based on specific information about the activity of each production line, for making an analysis its global efficiency, itself. Consequent to this, it was made the Pareto diagram for the most manufactured products prioritization in the October and November months, since it has innumerable products, such as, at being a machining enterprise and by being a production to order. Subsequently, it was performed processes, flows, man - machine and routes diagrams; it is following this, it was performed the plant layout redesign with the aim to improve found changes, resulting, an increase into production efficiency given the enterprise actual state. Further, it was performed the 5`S study its preliminary phase; constating, what the greatest impact changes for organization, which caused by automatic machines, such as: CNC lathes and machining centers.